Anterior Tarsal Tunnel Syndrome with Presence of Accessory Deep Peroneal Nerve: Case Report - Sanela Zukić; Osman Sinanović; Nermina Pirić; Harun Brkić; Mirsad Hodžić; Renata Hodžić; Mirza Baručija (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2015)
Entrapment neuropathy of the deep peroneal nerve, also recognized as anterior tibial nerve, typically occurs at the anterior ankle and dorsal foot. Compression of this nerve, which anatomically is inferior to the extensor retinaculum, is commonly referred to as anterior tarsal tunnel syndrome. This syndrome is rare and remains poorly diagnosed among clinical problems. A 25-year-old woman was referred to our outpatient clinic for a second opinion. She presented with a vague pain over the dorsomedial aspect of the foot which occasionally radiated into the first intertarsal space. Electromyography revealed moderate prolongation of distal latency and presence of accessory deep peroneal nerve (ADPN) with partially innervated extensor digitorum brevis. Our diagnosis was anterior tarsal tunnel syndrome, and surgical decompression of the anterior tarsal tunnel was performed. At the follow up three months later the symptoms where almost completely gone. One year after, there were still no symptoms. The ADPN is of great clinical and surgical importance. In the presence of ADPN, the lesion of the deep peroneal nerve spare the lateral portion of the EDB, leading to the possibility of an incorrect conclusion, as it was the case with our patient.